TRAINING NEEDS ON HEALTH COMMUNICATION AND EDUCATION ABOUT DIABETES AMONG VILLAGE HEALTH WORKERS IN VU THU DISTRICT, THAI BINH PROVINCE IN 2020 (Vietnam Journal of Community Medicine, 2021)
Objective: Identify training needs on health communication and education about diabetes among village health workers in Vu Thu district, Thai Binh province in 2020.Subjects: Village Health Worker and Head of Commune Health Station in the communes of Vu Thu district, Thai Binh province.Method: the epidemiological method described through the cross-sectional investigation, combine quantitative research and qualitative research.Results: 70.2% of village health workers had participated in training courses on communication skills - health education; The highest proportion of respondents saying that the training period was enough (76.8%), 95.6% of the respondents think that the content of each training course was appropriate for them, and 62.3% evaluated organizational form of the training class to attract students; 50.4% ofvillage health workers needed to be trained in health communication skills, 49.5% of village health workers needed to be trained in health counseling skills, 26.2% hoped to train communication skillsthrough loudspeakers, radio; The most difficulty of village health workers when participating in training / training was due to a matter of time (41.1%).
Keywords: Village Health Worker, diabetes, health communication and education; training needs